Integral mean δ-subharmonic functions and classes of almost regularly increasing - Tarasyuk S. І. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
Classes Λ_δ of functions of finite λ-type δ-subharmonic in R^m are investigated. A membership criterion that defines when a function belongs to the class Λ_δ expressed in terms of its integral q-means is established. Classes of entirely regular growth of functions that are δ-subharmonic in R^m are introduced and the behavior of these functions at infinity and the distribution of Riesz-associated measures are studied.